Helmintos del pez Dormitator maculatus (Osteichthyes: Eleotridae) de Alvarado, Veracruz, México - Montoya Mendoza, Jesús (2004)
Dormitator maculatus (n=184) was collected in the Alvarado Lagoon, Mexico during a year period (Oct. 1993-1994). In the helminthologic review, the presence of Clinostomum complanatum (82.3%), Neoechinorhynchus golvani (76.1%), Spiroxys sp. (21.3 %), and Camallanus sp. (6.2%) was registered. Reduction of the hematocrit caused by such infection is significant (t, α= 0.05).